The existential critical thinking test of Lima - Salinas, Natividad Espiritu (2019)
The Existential Critical Thinking Test of Lima built by Espíritu, Canales, Lunay Torres, explores the purpose of life, considering the essence of life and theintentionality of existence, investigating the objectives that pursues the person.The intentionality has the Pragmatic and Spiritual sub areas. The construct validitywas obtained considering the judgement of six experts and the results wereevaluated using the lawshe index. Fortynine university students participatedin a pilot study in which 5 items were eliminated. The participants were 387 university students and professionals from Lima, to whom the test was appliedin person using an intentional sampling. One item was eliminated. The test finallyresulted in 32 items, with an appropriate reliability index with Cronbach’s alphain the Essence area of .756, in the Pragmatic Intentionality Area of .884 and in theSpiritual Intentionality area of .825. Percentile and T-score norms were drawn upfor the different areas.